A relação de meronímia em uma ontologia jurídica - Minghelli, Thaís Domênica (Universidade do Vale do Rio dos Sinos, 2011)
According to the demand for more efficient computer systems when it comes to information retrieval, as well as the large number of legal sites, ontologies have proved to be useful in this regard. Based on this scenario, this work aims to investigate the role of meronymy relationship to organize the content of Criminal Procedural Law, especially the procedure of trial by jury in order to place them in a legal linguistic ontology. For this, LRI-core ontology is studied, getting inspiration from it to create core categories to base the research and structure the domain modeling. The research is based in lexical semantics and the meronymy classification of Winston et. al. (1987). Relying on the Code of Criminal Procedure as the main research corpus, linguistic expressions are selected and analyzed under the part-whole perspective. Finally, there are illustrations abouthow data can be represented on the ontology editor Protégé. The result of this investigation shows that the meronymy relationship plays an important role as an organizing relationship of the content area of criminal procedural law, and thus it is relevant to knowledge representation and its recovery by means of ontologies.
Keywords: Ontologia; Direito; Meronímia; Categorias; Ontology; Law; Meronymy; Categories; ACCNPQ::Lingüística, Letras e Artes::Lingüística